2020
DOI: 10.1038/s41598-020-68486-1
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of sperm RNA processing for developmental research

Abstract: Recent studies have demonstrated the significance of sperm RNA function as a transporter of important information directing the course of life. To determine the message contained in sperm RNA, it is necessary to optimize transcriptomic research tools. The current study was performed to optimize the processing of sperm RNA from sample storage to quantitative real-time PCR and assess the corresponding method with to evaluate male fertility and its representative markers, equatorin (EQTN) and peroxiredoxin (PRDX)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…However, the amount of DNA is generally low in cell‐free samples, including urine (Oreskovic et al., 2019 ; Streleckiene et al., 2018 ). As the RNA content of EV samples is also low in comparison to cell or tissue RNA and the DNAse treatment reduces RNA yields (Norhazlin et al., 2015 ; Pang et al., 2020 ), the risk of losing the precious EV‐RNA due to the treatment is high. We thus regarded relevant to investigate the necessity of the DNAse treatment by analysing RNA yield and mRNA‐seq results from uEV.…”
Section: Discussionmentioning
confidence: 99%
“…However, the amount of DNA is generally low in cell‐free samples, including urine (Oreskovic et al., 2019 ; Streleckiene et al., 2018 ). As the RNA content of EV samples is also low in comparison to cell or tissue RNA and the DNAse treatment reduces RNA yields (Norhazlin et al., 2015 ; Pang et al., 2020 ), the risk of losing the precious EV‐RNA due to the treatment is high. We thus regarded relevant to investigate the necessity of the DNAse treatment by analysing RNA yield and mRNA‐seq results from uEV.…”
Section: Discussionmentioning
confidence: 99%
“…Sperm RNA was isolated according to a previous study [ 38 ]. Briefly, sperm numbers were adjusted to 40–50 × 10 6 cells/mL.…”
Section: Methodsmentioning
confidence: 99%
“…Many factors determine the results of the transcriptomic analysis. Pang et al [ 27 ] found that the average RNA concentration of sperm with DNase was 56% lower in the 15 min of incubation treatment with DNase (44.28 ± 8.12 ng/µL) than without DNase (101.7 ± 13.5 ng/µL) but produced a RNA quality that was not different between treatment with DNase (1.79 ± 0.03) and without DNase (1.80 ± 0.01). Using an RNA stabilizer solution is also considered significant [ 42 ].…”
Section: Sperm Transcriptome Analysis: Principles Regulation Applicat...mentioning
confidence: 99%
“…Sperm RNA has been identified in many mammalian species, such as humans, cattle, pigs, horses, and rodents. Some of the functions of sperm RNA include contributing during fertilization by delivering new paternal RNA to the oocyte and signaling in mitochondrial translation [ 27 ]. This sperm transcriptome also has an important role in the developmental stages of cell division in oocytes after fertilization and placenta development [ 26 ], zygote development [ 28 ], early embryonic development [ 29 ], and even epigenetic inheritance between generations [ 30 ].…”
Section: Introductionmentioning
confidence: 99%